Two prophylactic medication approaches in addition to a pain control regimen for early medical abortion < 63 days' gestation with mifepristone and misoprostol: study protocol for a randomized, controlled trial. Issue 1 (December 2016) - Dragoman, Monica; Grossman, Daniel; Kapp, Nathalie; Huong, Nguyen; Habib, Ndema; Dung, Duong; Tamang, Anand
Abstract Background Pain is often cited as one of the worst features of medical abortion. Further, inadequate pain management may motivate some women to seek unnecessary clinical care. There is a need to identify effective methods for pain control in this setting. Methods/Design We propose a randomized, placebo-controlled trial. 576 participants (288 nulliparous; 288 parous) from study sites in Nepal, South Africa and Vietnam will be randomly allocated to one of three treatments: (1) ibuprofen 400 mg PO and metoclopramide 10 mg PO; (2) tramadol 50 mg PO and a placebo; or (3) two placebo pills, to be taken immediately before misoprostol and repeated once four hours later. All women will be provided with supplementary analgesia for use as needed during the medical abortion. We hypothesize that women receiving prophylactic analgesia will report lower maximal pain scores in the first 8 h following misoprostol administration compared to women receiving placebos for medical abortion through 63 days' gestation. Our primary objective is to determine whether prophylactic administration of ibuprofen and metoclopramide or tramadol provides superior pain relief compared to analgesia administration after pain begins, measured during the first eight hours after misoprostol administration. Secondary objectives include identifying covariates associated with higher reported pain scores; determining any impact of the study medicines on medical abortion success; and, qualitatively exploring women's physical experiences of medical abortion, especially related to pain, and how can they be improved. Data sources include medical records, participant symptom diaries and interview data obtained on the day of enrollment, during the medical abortion, and at follow-up. Participants will be contacted via telephone on day 3 and return for follow-up will occur approximately 14 days after mifepristone, concluding study participation. A subset of 42 women will also be invited to undergo in-depth qualitative interviews following study completion. Discussion Although pain is one of the most common side effects encountered with medical abortion, little is known about optimal pain management for this process. This multi-arm trial design offers an efficient approach to evaluating two prophylactic pain management regimens compared to use of pain medication as needed. Trial registration ACTRN12613000017729 (Prospectively registered 8/1/2013).